Range limits in sympatric cryptic species: a case study in Tetramorium pavement ants (Hymenoptera: Formicidae) across a biogeographical boundary. Issue 2 (2nd August 2018) - Cordonnier, Marion; Bellec, Arnaud; Dumet, Adeline; Escarguel, Gilles; Kaufmann, Bernard
Abstract: In the context of climate changes, factors that determine the distribution patterns of European species of the ubiquitous ant genus Tetramorium were investigated. The study took place along a steep North‐South climatic gradient across the boundary between the European Continental and Mediterranean biogeographical regions spanning 460 km along the Rhône valley, France. Ants from 1690 Tetramorium colonies were collected in 19 sampling zones. Species were identified using an integrative approach based on a two‐step process combining nuclear DNA (14 microsatellite markers), morphological examination and mitochondrial DNA cytochrome oxidase I sequencing. The impact of climate on species distribution patterns was tested using bioclimatic variables. Species discrimination was successful, despite a complex situation with cryptic species, inter‐specific hybridisation and uneven sampling across species. Our results showed a strong effect of latitude, temperature and rainfall on the distribution of three of four species. Tetramorium semilaeve was found only south of the boundary, in warmer and dryer sites; Tetramorium caespitum extended north and 70 km south of the boundary and favoured colder sites with strong seasonal variation. Tetramorium immigrans was absent from the northernmost sampling zones and favoured warmer and wetter sites. Tetramorium moravicum was mostly found close to the boundary, but without significant climatic preferences. The fundamental role of climate as a factor limiting the ranges of these species at a major biogeographical boundary is confirmed. Monitoring range limits of these strongly climate‐dependant species may offer exciting insights on the impact of climate changes on species distributions.